Molecular confirmation of Lassa fever imported into Ghana - Joseph H.K. Bonney; Edward O. Nyarko; Sally-Ann Ohene; Joseph Amankwa; Ralph K. Ametepi; Shirley C. Nimo-Paintsil; Badu Sarkodie; Prince Agbenohevi; Michael Adjabeng; Nicholas N.A. Kyei; Samuel Bel-Nono; William K. Ampofo (AOSIS, 2016)
Background: Recent reports have shown an expansion of Lassa virus from the area where it was first isolated in Nigeria to other areas of West Africa. Two Ghanaian soldiers on a United Nations peacekeeping mission in Liberia were taken ill with viral haemorrhagic fever syndrome following the death of a sick colleague and were referred to a military hospital in Accra, Ghana, in May 2013. Blood samples from the soldiers and five asymptomatic close contacts were subjected to laboratory investigations. Objective: We report the results of these investigations to highlight the importance of molecular diagnostic applications and the need for heightened awareness about Lassa fever in West Africa. Methods: We used molecular assays on sera from the two patients to identify the causativeorganism. Upon detection of positive signals for Lassa virus ribonucleic material by two differentpolymerase chain reaction assays, sequencing and phylogenetic analyses were performed. Results: The presence of Lassa virus in the soldiers' blood samples was shown by L-gene segment homology to be the Macenta and las803792 strains previously isolated in Liberia, with close relationships then confirmed by phylogenetic tree construction. The five asymptomatic close contacts were negative for Lassa virus. Conclusions: The Lassa virus strains identified in the two Ghanaian soldiers had molecular epidemiological links to strains from Liberia. Lassa virus was probably responsible for the outbreak of viral haemorrhagic fever in the military camp. These data confirm Lassa fever endemicity in West Africa.